Evaluating the phenolic composition and antioxidant properties of Georgia pecans after in vitro digestion. (February 2023) - Cheung, Michelle; Robinson, Julie A.; Greenspan, Phillip; Pegg, Ronald B.
Abstract: Acetonic crude extracts from raw and roasted Georgia pecans were prepared and subjected to in vitro gastrointestinal digestion. Digested and undigested extracts of raw pecan phenolics were then separated into low- and high-molecular-weight (LMW and HMW) fractions via Sephadex LH-20 column chromatography; afterwards, they were characterized by RP-HPLC-ESI-MS. The LMW fraction consisted primarily of flavan-3-ols and ellagic acid derivatives and following digestion there was an overall loss in phenolics from 16% to 100%. In the HMW fraction, procyanidins with degrees of polymerization ranging from dimers to hexamers were present. Following digestion, a loss in higher oligomeric procyanidins was observed, along with a significant increase in quantity of dimers. This increase was attributed to the dimerization of (+)-catechin/(−)-epicatechin and the scission of larger procyanidins, mainly tetramers to hexamers. The loss of phenolics following digestion, as seen by HPLC characterization, was reflected in reduced total phenolics content and antioxidant capacity, as determined by selected in vitro antioxidant assays. Highlights: Pecan phenolics, both pre- and post-digestion, exhibited antioxidant activity. Digested phenolics were separated into low- and high-molecular-weight fractions prior to MS analysis. The oligomeric procyanidin profile changed markedly after in vitro digestion. Dimer levels increased at the expense of procyanidins with greater degrees of polymerization.